Skiing Trauma and Safety: Twelfth Volume 1999
DOI: 10.1520/stp12366s
|View full text |Cite
|
Sign up to set email alerts
|

Femur Fractures in French Winter Sports Resorts

Abstract: This paper presents the study of the incidence of femur fractures and their epidemiological description in the French winter sports resorts. During the 1994, 1995, and 1996 seasons, 99.339 injuries were recorded by the 72 physicians of the “Médecins de Mon- tagne” Skiing Safety Network. These physicians are divided into 52 winter sports resorts. Their distribution is homogeneous across the entire French mountainous regions. During the 1994 season and in the Northern Alps region, we have studied the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…There is evidence that a greater ski length increases the likelihood of sustaining an ACL injury 6 8 9. In line with these studies, we also found an increasing likelihood of sustaining an ACL injury with increasing ski length in the multiple regression analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There is evidence that a greater ski length increases the likelihood of sustaining an ACL injury 6 8 9. In line with these studies, we also found an increasing likelihood of sustaining an ACL injury with increasing ski length in the multiple regression analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has shown that ski geometry may be related to ACL injury risk. For example, a greater ski length increases the likelihood of sustaining an ACL injury,6 8 9 but the mean side-cut radius has not differed significantly between ACL injured and uninjured recreational skiers 9. Because the side-cut radius of a ski depends on the widths of the tip, waist and tail, it is possible that skis of the same lengths and side-cut radius differ within the three width dimensions 10.…”
Section: Introductionmentioning
confidence: 99%